Food Force: the first humanitarian video game. (Journal of Parents and Teachers, 2014)
The fundamental goal of the Food Force video game is to get humanitarian aid to those who need it. The game consists of different missions in which children from 8 to 13 years will face different situations to help the most disadvantaged.
Keywords: Video game; Food Force; humanitarian aid.